Speech competence – the basis of modern preparation of future teachers of humanities - Вигранка, Т. В. (Scientific notes of the pedagogical department, 2017)
The article analyzes the characteristics and key features of the model of language competence as part of academic education of modern specialists of humanitarian description. Theoretical principles carried review features the use of language competencies of academic education for professionals. Grounded speech and basic components of linguistic and communicative competence provide professional trade specialists of humanitarian description.